Learning Chinese, turning Chinese : challenges to becoming sinophone in a globalised world - McDonald, Edward, 1963- (Asia's transformations., 2011)
In this book Edward McDonald takes a fresh look at issues of language in Chinese studies. He takes the viewpoint of the university student of Chinese with the ultimate goal of becoming 'sinophone': that is, developing a fluency and facility at operating in Chinese-language contexts comparable to their own mother tongue. While the entry point for most potential sinophones is the Chinese language classroom, the kinds of "language" and "culture" on offer there are rarely questioned, and the links between the forms of the language and the situations in which they may be used are rarely drawn. The